ECG Quiz no. 22 - Okreglicki, A (SA Heart Journal, 2017)
A 77-year-old man with no past medical history was referred with a one year history of episodes of prolonged palpitations for further management. The palpitations, which are not particularly fast, are associated with uncomfortable pulsations in the neck. Two ECGs were recorded, one before seeing the doctor and the second after the consultation.